INTER-SECTOR AND INTER-COUNTRY LINKAGES IN INDONESIAN ECONOMY: WORLD INPUT-OUTPUT ANALYSIS - Muchdie, Muchdie; Imansyah, Muhammad Handry (Muhammadiyah University Press, 2019)
Results of analysis on inter-sector and inter-country linkages in Indonesian economy using world input-output data for the years 2000, 2005, 2010, and 2014 are provided in this paper. The model was aggregated into 30 sectors and 8 countries. Inter-sector linkages are analyzed using forward and backward effect indices, and then sectors were grouped into 4 groups. Meanwhile inter-county linkage is analyzed is spill-over and feed-back effects. The results showed that firstly, number of sectors include in Group-1, namely key sectors with strong forward and backward linkages: two sectors in year 2000, one sector in year 2005, 8 sectors in year 2010 and 2014. Secondly, spill-over effects were significantly importance in Indonesia economy, as around 20 per cent of multipliers occurred in other countries: 19.74 per cent in year 2000; 20.25per cent in year 2005; 18.19 per cent in year 2010 and20.64 per cent in year 2014. Only small feed-back effects are in Indonesian economy; in average 0.12 per cent in year 2000; 0.14 per cent in year 2005; 0.15 per cent in year 2010 and 0.15 per cent in year 2014. Finally, ignoring inter-country feed-back could be misleading as error created was significant.